An economic analysis of adjusted gross Revenue-Lite insurance on farm income variability for southeast Kansas farms - Saffert, Andrew Thomas (Kansas State University, 2007)
In today’s production agricultural sector, managing risk is essential to insuring the economic well being and sustainability of successful enterprises. Considering the inherent risks present in today’s agricultural arena, risk management has become the central focus of discussions for policy makers and producers alike. Therefore the objective of this research paper is to examine the impact a whole-farm adjusted gross revenue insurance risk management program (AGR-Lite) has on reducing farm income variability using historical farm level data for Southeast Kansas farms. A panel data set of actual farm level income data was compiled to evaluate the impact of AGR-Lite on farm income variability for 219 Southeast Kansas farms. Although actual income tax records were not available annual data over the period 1993 to 2005 from the Kansas Farm Management Association was used to reproduce the essential information a farm manager would need from IRS form 1040 schedule F and inventory records to purchase AGR-Lite (Langemeier, 2003). Income distributions for each farm from 1999 to 2005 were calculated for two strategies; the farm manager did not insure and the manager insured each year using AGR-Lite as a stand-alone product. The AGR-Lite insurance strategy assumed a 75% coverage level and 90% payment rate. The income distributions were compared using three premium scenarios. In general, the results of this study reveal participation in the AGR-Lite program, in most instances, reduced standard deviation, Coefficient of Variation (CV), and Downside Risk (DR). Additionally average minimums and Certainty Equivalents (CE) were increased with the product. The following results reflect application of Actuarially Fair Average Rate for farms with Indemnities (AFARI), which is believed to reflect actual market performance. Additionally the following reflects results using Net Farm Income (NFI). Results reveal that purchasing AGR-Lite reduced standard deviations 7.01%, 11.34%, 0.29%, and 2.53% for total, crop, livestock, and dairy farms assuming AFARI. However beef farms were the lone category to sustain a 0.81% standard deviation increase. Despite reductions in absolute variability, relative risk (CV) increased 18.94%, 17.12%, 53.84%, and 3.19% for total, livestock, beef, and dairy. Crop farms were the only category to generate a CV reduction (9.52%). Under AFARI crop farms generated the largest minimum increase, reducing downside risk, by 69.97%. For total and dairy farm categories average minimums increased 62.93% and 0.60%. The remaining farm categories, livestock and beef, yielded 65.07% and 57.03% reductions to average minimum.
Keywords: Insurance; Risk Management; AGR-Lite; Agriculture, General (0473)